Analisis Strategi Adaptasi Masyarakat Terhadap Bencana Banjir di Kawasan Perumahan Wisma Tropodo, Kecamatan Waru, Kabupaten Sidoarjo - Marsya Divani Anggraeni; Nugroho Hari Purnomo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The research was conducted with the aim of analyzing the adaptation strategies undertaken by the community and the level of effectiveness of their implementation in facing flood disasters in the Wisma Tropodo Housing Complex, Waru District, Sidoarjo Regency. This research used a descriptive method with a quantitative approach. The research data were obtained through observation, interviews, and questionnaires distributed to 95 respondents of Wisma Tropodo Housing residents. Data analysis was carried out by describing the frequency distribution and percentage of each research variable using tables. The results showed that the Wisma Tropodo Housing community in an effort to face flood disasters adapted by raising roads, house foundations, using water pumps, and repairing and optimizing the drainage system. Analysis of the level of effectiveness of the adaptation strategy of raising roads and house foundations showed less effective results because there were still shortcomings in the form of the nature formed from the implementation of the adaptation strategy was only temporary. Meanwhile, the adaptation strategy of using water pumps and repairing and optimizing the drainage system showed effective results because there were advantages in the form of the ability of these adaptation strategies to directly resolve the root of the problem.